2020
DOI: 10.3390/biomedicines8010008
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome and Type 2 Diabetes Mellitus: Discussing A Complex Relationship

Abstract: Type 2 diabetes mellitus (T2DM) is a disease that affects over 9% of the United States population and is closely linked to obesity. While obesity was once thought to stem from a sedentary lifestyle and diets high in fat, recent evidence supports the idea that there is more complexity pertinent to the issue. The human gut microbiome has recently been the focus in terms of influencing disease onset. Evidence has shown that the microbiome may be more closely related to T2DM than what was originally thought. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 53 publications
4
95
2
6
Order By: Relevance
“…Similar experiments in separate studies also revealed the indirect role of the mammalian target of rapamycin complex 1 (mTORC1), mediated by the amount of 4E-binding protein 1 (4E-BP1), again supporting the notion of a more resilient cell towards metabolic abrogation and, thus, metabolic syndrome [79]. Finally, recent developments have identified the microbiome as a key player/target for intervention, especially from a precision medicine perspective, for the potential risk modulation of metabolic syndrome and T2DM [70].…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Similar experiments in separate studies also revealed the indirect role of the mammalian target of rapamycin complex 1 (mTORC1), mediated by the amount of 4E-binding protein 1 (4E-BP1), again supporting the notion of a more resilient cell towards metabolic abrogation and, thus, metabolic syndrome [79]. Finally, recent developments have identified the microbiome as a key player/target for intervention, especially from a precision medicine perspective, for the potential risk modulation of metabolic syndrome and T2DM [70].…”
mentioning
confidence: 80%
“…It is believed that an excess of reactive oxygen species form and transfer unpaired electrons, which then results in the oxidation of cellular machinery. In a healthy individual, antioxidants counter this process, but imbalance results in oxidative stress, glycation, and increased insulin resistance (Figure 1) [14,50,70,71].…”
Section: Concurrent Therapies For Type 2 Diabetes Mellitus and Sarcopmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that exposure to As not only induces disturbances in the abundance and composition of bacterial communities but also affects their metabolomic profile, which subsequently results in the disturbance of host metabolite homeostasis. These changes in metabolite homeostasis are important risk factors involved in tissue dysfunctions, which may cause diseases such as obesity and diabetes [139]. [43] reported that perinatal lead (Pb) exposure (32 ppm) in the drinking water, in wild-type non-agouti (a/a) mice of the Avy strain isogenic mouse model of perinatal environmental exposure, induced changes in the adult offspring gut microbiota.…”
Section: Metalsmentioning
confidence: 99%
“…In fact, regular consumption of artificial sweeteners has been associated with decreased satiety, altered glucose homeostasis and increased caloric intake and obesity in adults [ 32 , 35 ]. There is also significant evidence that artificial sweeteners change the gut microbiota in a non-favorable fashion thus increasing risk for obesity, T2DM, and CVD as the microbiota extends impact on those metabolic pathologies [ 36 ].…”
Section: Health Effects Of Non-alcoholic Beveragesmentioning
confidence: 99%